Airborne and ground based CCN spectral characteristics: Inferences from CAIPEEX – 2011. (January 2016) - Varghese, Mercy; Prabha, Thara V.; Malap, Neelam; Resmi, E.A.; Murugavel, P.; Safai, P.D.; Axisa, Duncan; Pandithurai, G.; Dani, K.
Abstract: A first time comprehensive study of Cloud Condensation Nuclei (CCN) and associated spectra from both airborne and ground campaigns of the Cloud Aerosol Interaction and Precipitation Enhancement Experiment (CAIPEEX) conducted over the rain shadow region of Western Ghats during September and October 2011 is illustrated. Observations of CCN spectra during clean, polluted and highly polluted conditions indicated significant differences between airborne and ground observations. Vertical variation of CCN concentration is illustrated from airborne observations in the clean, polluted and highly polluted conditions with different air mass characteristics. The cloud base CCN number concentrations are three times less than that of the surface measurements at different supersaturations. Diurnal variations of the ground based CCN number concentration and activation diameter showed bimodality. Atmospheric mixing in the wet conditions is mainly through mechanical mixing. The dry conditions favored convective mixing and were dominated by more CCN than the wet conditions. New particle formation and growth events have been observed and were found more often on days with convective mixing. The average critical activation diameter (at 0.6% SS) observed at the ground is approximately 60 nm and availability of a large number of particles below this limit was due to the new particle formation. Observations give convincing evidence that the precipitable water and liquid water path is inversely proportional to surface CCN number concentration, and this relationship is largely dictated by the meteorological conditions. Highlights: Co-located CCN spectral characteristics at the cloud base and at the ground level. Surface CCN concentration decreases as liquid water path increases. New particle formed are below the critical activation diameter of ≈60 nm. Mechanical mixing during wet days and convective mixing during dry days. Short time variations in dynamics and cloud characteristics impact surface CCN.